Effects of Dursban on Sexual Hormones and Changes of Testis Tissue in Mice - E Fattahi (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2013)
ABSTRACTBACKGROUND AND OBJECTIVE: Dursban is the most common organophosphate pesticides that used for control of pests. The main action of this compound is inhibition of cholinesterase enzyme, which adversely effects on reproductive system. Due to the use of pesticides in agriculture and the possible damage, the effect of this toxin on the sexual hormones and changes of testis tissue in mice was studied.METHODS: In the experimental study, 40 adult male mice were divided into four equal groups including control, sham, experimental (1and 2) groups. In the experimental groups, animals were intraperitoneally injected with consecutive doses of 15mg/kg and 30mg/kg dursban for one month (five days per week). The olive oil was injected to sham group and control received no injection. Testes tissue sections were prepared to investigate possible changes occurring in the category of spermatogenic, Leydig cells and seminiferous tubule by eye piece (calibrated ocular lens). Diameter of testis was measured by micrometer. Levels of gonadotropin hormones and testosterone were assayed by radioimmunoassay. Then data were analyzed. FINDINGS: Levels of gonadotropin hormones and testosterone in experimental (1 and 2) groups were significantly declined compared to control and sham group (p<0.05). The number of spermatogonia, primary and secondary spermatocyts, spermatids, Leydig cells, diameter of testis and seminiferous tubule diameter in the experimental (1 and 2) groups compared to control and sham group and also in the experimental 2 group compared to experimental 1 group were decreased (p<0.05). CONCLUSION: These results demonstrated that dursban can cause the decrease of sexual hormones and damage of testes tissue that is pushing people toward infertility.